Is there a place for nutritional supplements in the treatment of idiopathic male infertility? - Davide Arcaniolo; Vincenzo Favilla; Daniele Tiscione; Francesca Pisano; Giorgio Bozzini; Massimiliano Creta; Giorgio Gentile; Filippo Menchini Fabris; Nicola Pavan; Italo Antonio Veneziano; Tommaso Cai (Archivio Italiano di Urologia e Andrologia, 2014)
Objective: Infertility affects 15% of couples in fertile age. Male factor is a cause of infertility in almost half of cases, mainly due to oligoasthenoteratozoospermia (OAT). The purpose of this study is to review the effects of nutritional supplements as medical treatment for idiopathic male infertility. Material and methods: A Pub Med and Medline review of the published studies utilizing nutritional supplements for the treatment of male infertility has been performed. Results: Clinical trials on Vitamin E, Vitamin A, Vitamin C. Arginine, Carnitine, N-Acetyl-Carnitine, Glutathione, Coenzyme Q10, Selenium and Zinc were reviewed. Although there is a wide variability in selected population, dose regimen and final outcomes, nutritional supplements both alone and in combination seems to be able to improve semen parameters (sperm count, sperm motility and morphology) and pregnancy rate in infertile men. Conclusions: There are rising evidences from published randomized trials and systematic review suggesting that nutritional supplementation may improve semen parameters and the likelihood of pregnancy in men affected by OAT. This improvement, however, is not consistent and there is a wide variation in the treatment regimens used. Well designed and adequately powered RCTs are needed to better clarify the role of nutritional supplements as treatment for male infertility.